Inhibition of miR-182-5p attenuates pulmonary fibrosis via TGF-β/Smad pathway. (May 2020) - Chen, Y; Zhang, Q; Zhou, Y; Yang, Z; Tan, M
Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease with high morbidity and mortality. miR-182-5p is overexpressed in several fibrosis-related diseases but its effect in pulmonary fibrosis has not been reported yet. To investigate the function of miR-182-5p in pulmonary fibrosis, we established bleomycin (BLM)-induced fibrotic mice model and transforming growth factor-β1 (TGF-β1)-treated human embryonic lung fibroblasts model. In this study, miR-182-5p was highly expressed in pulmonary tissues of BLM-induced fibrotic mice. The content of hydroxyproline and TGF-β1 was decreased by downregulating the expression of miR-182-5p, indicating that fibrosis was alleviated in mice treated with Lentivirus-anti-miR-182-5p.Quantification of fibrosis-related proteins demonstrated that downregulation of miR-182-5p inhibited the expression of profibrotic proteins (fibronectin, α-smooth muscle actin, p-Smad2/p-Smad3) as well as enhanced the level of Smad7. In vitro assays validated that miR-182-5p was induced by TGF-β1 with the function of promoting fibrosis. In dual-luciferase reporter assay, Smad7 was demonstrated to be negatively regulated by miR-182-5p. Moreover, the effect of knocking down miR-182-5p on inhibiting fibrosis was achieved by upregulating the expression of Smad7. Therefore, miR-182-5p can be regarded as a biomarker of IPF and its inhibition may be a promising therapeutic approach in treating IPF.